The Social Landscape of Education in Rural Areas: Evening Study Programs, Study Irregularities and Academic Achievement - Leasa, Marleny; John Rafafy Batlolona; Elsina Titaley; Thopilus Batlolona (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Rural schools in each region face a number of challenges unique to their environment. Challenges in the form of student irregularity in evening study. They spend their evenings accessing social media, which has a negative impact on academic performance. Therefore, the action taken by the school is to implement an evening study program. Therefore, the aim of the research analyze evening study programs and student study regularity in rural areas which have implications for student academic achievement. This type of research is a qualitative study in the form of a case study on junior high school students. The subjects involved in the research are junior high school principals, teachers, village heads, village officials, and parents of students in grades one to three. The data collection method is observation. The data analysis method used was descriptive qualitative. The results of the research show that with the evening study program, there is regularity in learning and student achievement increases and is better. Apart from that, it was found that at night no students were found outside the house. They spend time studying at the teacher's house at four points that have been prepared for learning. Apart from that, parents are no longer afraid because every night the student's condition is well controlled so that it does not have a negative impact. Therefore, it can be recommended that evening study programs in rural areas can improve learning regularity, academic achievement and student personality traits. Implications of this research can be the basis for formulating policies that are more inclusive and adaptive to the needs of rural communities, especially in terms of organizing evening study programs.